A glimmer of hope for a devastating complication - Beynon, Christopher (Blood, 2017)
In this issue of Blood, Lopes et al report that patients with atrial fibrillation suffered from intracerebral and subdural hemorrhage less frequently when they were treated with apixaban than with warfarin, despite the warfarin anticoagulation being within therapeutic ranges in the majority of cases.1
Published online June 1, 2017
Gesehen am 18.06.2018